Implementation of rapid entire body assessment and anthropometry methods in conveyor design - Nismah Panjaitan; Felica Felica (Jurnal POLIMESIN, 2023)
The packaging station is one of the stations needed to produce the product. The workers in this station are still doing the process manually. The packaging station has several processes, namely the weighing process, the sewing process, and the moving process of the finished product by manually lofting the sack from the sewing machine to the pallet. The moving process has three activities holding, lifting, and moving. Workers who work manually often complain of pain felt while working, so they are at risk of experiencing musculoskeletal disorders. Accordingly, it is important to analyse the work posture to determine whether improvements must be made. The Rapid Entire Body Map (REBA) analyses the work position. Analysis of work posture is moving the product. The REBA method's posture assessment results are 8 for holding, 9 for lifting, and 10 for moving. From the results, it can be categorized as a high-risk level, and immediate improvements are needed. The improvements were made by designing a conveyor from the sewing machine to the pallet using the Anthropometric method with dimensions of 100cm, width of 65cm, and height of 113cm.